Density, Refractive Index, Apparent Specific Volume, and Electrical Conductivity of Aqueous Solutions of Poly(ethylene glycol) 1500 at Different Temperatures - Costa, Bernardo de Sa; Garcia-Rojas, Edwin Elard; Reis Coimbra, Jane Selia dos; Teixeira, Jose Antonio; Telis-Romero, Javier [UNESP] (Amer Chemical Soc, 2014)
Thermophysical properties of aqueous solutions of poly(ethylene glycol) 1500 g.mol(-1) were measured as a function of polymer concentration w = (0.05, 0.10, 0.15, 0.20 and 0.25) and temperature T/K = (288, 293, 298, 303 and 308). Aqueous systems composed of poly(ethylene glycol) are frequently used in processes involving the separation of biological compounds. The density of the solutions varied from (1001.68 to 1042.65) kg.m(-3), the refractive index ranged from (1.3377 to 1.3681), the apparent specific volume was between (0.8336 and 0.8528) g.cm(-3), and the electrical conductivity varied between (66.22 and 170.29) 10(-3) mS.cm(-1). Polynomial models for the properties as a function of temperature and poly(ethylene glycol) 1500 g.mol(-1) concentration were fitted to the experimental data. Models accounting for combined effects between variables are particularly useful in industrial applications in which physical parameters must be promptly and accurately calculated.